2019
DOI: 10.3390/ijms20153647
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Disturbances in Dementia and Beyond: Time for a New Conceptual Frame?

Abstract: Alzheimer’s disease and vascular dementia are estimated to be the most common causes of dementia, although mixed dementia could represent the most prevalent form of dementia in older adults aged more than 80 years. Behavioral disturbances are common in the natural history of dementia. However, so far, there is a paucity of studies that investigated the causal association between behavioral psychological symptoms of dementia and dementia sub-types, due to the high heterogeneity of methodology, study design and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Therefore, the external validity of this finding is limited. In accordance with previous reports [26, 33], there was also consensus in our study regarding the need to have protocols for the use of atypical antipsychotics for BPSD in order to help physicians in clinical practice and in benefit of patients and their families, a finding that could indicate an insufficient knowledge or application of guidelines in practice [34-36].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the external validity of this finding is limited. In accordance with previous reports [26, 33], there was also consensus in our study regarding the need to have protocols for the use of atypical antipsychotics for BPSD in order to help physicians in clinical practice and in benefit of patients and their families, a finding that could indicate an insufficient knowledge or application of guidelines in practice [34-36].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the complete pharmacological profile and possible side effects (beyond cognitive) of donepezil remain poorly understood (Jelic and Darreh-Shori, 2010), necessitating further in-depth translational studies using both longterm and acute treatments. This problem is important since affective and other behavioral deficits are particularly common An acetylcholinesterase inhibitor, donepezil, increases anxiety and cortisol levels in adult zebrafish in AD patients (Ambrogio et al, 2019;Khachaturian and Radebaugh, 2019), yet there are no established and approved pharmacotherapies to treat these deficits (Khachaturian and Radebaugh, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the dementia subtypes do not present differences in terms of behavioral and psychological symptoms. The intensity of neuropsychiatric symptoms in dementia subtypes may fluctuate over time, and several factors, including various underlying neurobiological changes, comorbidities, pathologies in cerebral vascularization, and age play a role in such fluctuations [22]. In addition to cognitive loss, Alzheimer's disease also presents symptoms such as behavioral changes, psychosis, mood swings, apathy, agitation, and abnormal motor behaviors [23].…”
Section: Discussionmentioning
confidence: 99%